Studi Kekasaran Permukaan Produk Investmen Casting Aluminium Minuman Kaleng Bekas Dengan Parameter Temperatur Tuang Dan Ukuran Butir Lempung - Adri, Adri; Masnur, Dedy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Rarefaction inside of intake manifold can improve motorcycles engine performance. Intake manifold produce by sand casting method limited for low surface roughnes. Investment casting method might produce low surface roughnes, therefore further study must carried out to observe process parameters namely pouring temperatures and clay grain size. Current study has carried out in order to observe the influence pouring temperatures and clay grain size on surface roughness. Aluminium beverage tins and local natural clay were use raw material for molding. The clay sieved to obtain grain sizes of 60, 100, 200 mesh respectively. The wax clusters were coated with ceramic slurry up to 10 mm thickness and final coat was with sika to strengthen the mould. The ceramic shell were dewaxed at 120ºC and then sintered at 350ºC for 60 minutes. Aluminium beverage tins were cast atthe pouring temperatures 650, 700, and 750°C. The surfaces products tested by surface roughness tester. Theresults show the surface roughness increases as the pouring temperature increase. At pouring temperature 650°C to 700°C was 7.15%, while at pouring temperature 650oC to 750oC was 130.27%. Surface roughness increases as the clay grain size decreases. At clay grain size 60 to 100 mesh was 8.24, while at clay grain size 60 to 200 mesh was 186.93%.Keywords: Investment casting, surface roughness, clay